Intrinsic network activity reflects the fluctuating experience of tonic pain. (13th January 2022) - Deak, Bettina; Eggert, Thomas; Mayr, Astrid; Stankewitz, Anne; Filippopulos, Filipp; Jahn, Pauline; Witkovsky, Viktor; Straube, Andreas; Schulz, Enrico
Abstract: Although we know sensation is continuous, research on long-lasting and continuously changing stimuli is scarce and the dynamic nature of ongoing cortical processing is largely neglected. In a longitudinal study, 38 participants across four sessions were asked to continuously rate the intensity of an applied tonic heat pain for 20 min. Using group-independent component analysis and dual regression, we extracted the subjects' time courses of intrinsic network activity. The relationship between the dynamic fluctuation of network activity with the varying time courses of three pain processing entities was computed: pain intensity, the direction of pain intensity changes, and temperature. We were able to dissociate the spatio-temporal patterns of objective (temperature) and subjective (pain intensity/changes of pain intensity) aspects of pain processing in the human brain. We found two somatosensory networks with distinct functions: one network that encodes the small fluctuations in temperature and consists mainly of bilateral primary somatosensory cortex (SI), and a second right-lateralized network that encodes the intensity of the subjective experience of pain consisting of SI, secondary somatosensory cortex, the posterior cingulate cortex, and the thalamus. We revealed the somatosensory dynamics that build up toward a current subjective percept of pain. The timing suggests a cascade of subsequent processing steps toward the current pain percept.